PENGARUH KEWAJARAN HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN WINA RUMAH KEBAYA - Ni Wayan Wina Premayani; Gede Agus Dian Maha Yoga (Widya Manajemen, 2019)
Along with the increase in the number of boutiques of Balinese kebaya, making competition in the kebaya industry increasingly high, and entrepreneurs are required to determine the marketing strategy planning that will be used to face the current competition. Consumer satisfaction is a very important thing to consider in facing the market competition of the Balinese kebaya industry. The number of samples representing the population in this study were as many as 75 consumers of Wina Rumah Kebaya. Data were analyzed by multiple linear regression analysis techniques, where the validity and reliability tests were carried out in the initial stages of testing. The results of this study are the price fairness and product quality partially have a significant effect on customer satisfaction, price fairness and product quality simultaneously also significantly influence customer satisfaction, and the prices fairness has the most dominant influence. For this reason, to increase customer satisfaction it is necessary to improve the quality of kebaya and consider the fairness of the price determined.